Teacher leadership and bullying management: a qualitative study of discipline in SJKC and SJKT schools in Kuala Pilah district - Hassan, Roshafiza; Chelliah, Gomathi (Macrothink Institute, 2025)
Bullying remains a prevalent issue in schools, affecting students across various backgrounds. While much focus has been placed on the victims and perpetrators, the role of teacher leadership in managing such discipline issues is critical yet under-explored. This study investigates how teacher leadership contributes to the management of bullying in Chinese (SJKC) and Tamil (SJKT) National Type Schools in the Kuala Pilah District. Using a qualitative approach, 10 teachers were interviewed using snowball sampling to gain insights into their leadership strategies and their role in student discipline. Findings suggest that teacher leadership, including reinforcement and punishment strategies, plays a vital role in curbing bullying and improving overall school discipline. The study highlights the importance of teacher intervention and leadership in maintaining school order and fostering a safer environment for students.